2009
DOI: 10.2215/cjn.05811108
|View full text |Cite
|
Sign up to set email alerts
|

Kidney Stones and the Risk for Chronic Kidney Disease

Abstract: Background and objectives: Kidney stones lead to chronic kidney disease (CKD) in people with rare hereditary disorders (e.g., primary hyperoxaluria, cystinuria), but it is unknown whether kidney stones are an important risk factor for CKD in the general population.Design, setting, participants, & measurements: Among Olmsted County, MN, residents, all stone formers (n ‫؍‬ 4774) whose condition was diagnosed in 1986 through 2003 were matched 1:3 to control subjects (n ‫؍‬ 12,975). Cox proportional hazards models… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
239
3
11

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 330 publications
(267 citation statements)
references
References 39 publications
14
239
3
11
Order By: Relevance
“…In a cohort of cystinuric patients, PCr appeared to increase with age (19). HBP and diabetes mellitus are risk factors for CKD in the general population (23) as well as in patients with nephrolithiasis (11,14,25,26). However, in a small series of cystinuric patients, it was reported that age and HBP were not significant risk factors for CKD (15).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…In a cohort of cystinuric patients, PCr appeared to increase with age (19). HBP and diabetes mellitus are risk factors for CKD in the general population (23) as well as in patients with nephrolithiasis (11,14,25,26). However, in a small series of cystinuric patients, it was reported that age and HBP were not significant risk factors for CKD (15).…”
Section: Discussionmentioning
confidence: 97%
“…The association between CKD and stones has been debated in many studies. The incidence and prevalence of CKD is significantly higher in patients with nephrolithiasis (11). However, the risk of CKD depends on the type of stones.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, clinical interpretations have mentioned not only an altering frequency and composition of urinary calculi but also a swing in gender and age-related incidences. Con tributing risk factors for kidney stones are obesity, insulin resistance and gastrointestinal pathology, living in warmer climates, and certain dietary patterns and medications [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…The proportion of kidney stone disease associated with ESRD approximately 3.2%. 5 Very limited evidence suggests that there is a relationship between kidney stones and the development into CKD, 6 and the kidney stone is a risk factor of ESRD not be clear. 7 Relationship between kidney stone and kidney function loss show that there is absolute increase in renal adverse outcomes associated with kidney stones.…”
Section: Introductionmentioning
confidence: 99%